ΜULTIPROXY PALEOENVIRONMENTAL RECONSTRUCTION: THE PIRAEUS COASTAL PLAIN CASE STUDY - Triantaphyllou, M.V.; Pavlopoulos, K.P.; Kouli, K.; Koukousioura, O.; Dimiza, M.D.; Aidona, E.; Syrides, G.; Pallikarakis, A.; Goiran, J.P.; Fouache, E. (Bulletin of the Geological Society of Greece, 2016)
The joint application of benthic foraminifera, pollen and non-pollen palynomorphs (NPPs), molluscs and magnetic susceptibility analyses in Piraeus coastal plain deposits resulted in the detailed study of palaeoenvironmental evolution of the area during almost the last 9000 years and the distinction of five lithostratigraphicalpaleoenvironmental units and subunits. Combined results of our analyses features the occurrence of an inner lagoon (unit Aa) followed by open lagoon (Unit Ab) depositional environment that was transformed to a shallow marine paleoenvironment with lagoonal features (Unit B) after 7800 BP. Since about 4800 BP a closed oligohaline lagoon (Unit C) used for grazing, occurred in the area, while after 2800 BP a marshy oligohaline depositional environment (Unit D) and signs of intensive agricultural activities are evidenced. The very good correlation of benthic foraminiferal, palynological, molluscan and magnetic susceptibility data and resulted indices is indicative of the potential of the applied methodologies as a paleoenvironmental tool box.